PENERAPAN SISTEM INFORMASI BERBASIS KOMPUTER SEBAGAI PENDUKUNG PELAYANAN PENDIDIKAN - Yulhendri, Yulhendri (Universitas Esa Unggul, 2017)
AbstractThe library is the most important infrastructure in the learning process in a schools. A good and complete library facility will support the success of the learning process. Community Service performed at Secondary School in Tanjung Duren Barat III No. 1 Jakarta, exactly Al Chasanah Educational Foundation aims to share knowledge or transfer knowledge using the application of information systems based on information technology as a support of education services to Teachers and Education Staff in order to understand and capable for the development of learning as needed. Specific targets to be achieved are the understanding and ability to implement computer-based information system as a supporter of education services at Yayasan Pendidikan Al Chasanah to be able to adjust from the demands and needs of the business world and industry, as supporters and library resources extension is also given on the implementation of school libraries at Al Chasanah Foundation with using opensource application of SliMS Senayan. The method used in the form of counseling with the delivery of the practical through the transfer of knowledge and serving the role and function of the library application to improve education services so that really can be accepted and increase the essence of knowledge and skills of Teachers and Librarians and especially for students. The results of community service activities conducted by the P2M Team Fasilkom Esa Unggul University held in the school environment that is in Al Chasanah Foundation is an increase and development of insight for teachers and librarians related to the functions and processes of library management in the school environment under the foundation Al Chasanah. Coupled with the use of Opensource Library Information System Software SliMS Senayan, the function and process of school library management can be more optimized. Keywords : school library, open source, librarian AbstrakPerpustakaan merupakan infrastruktur yang paling penting dalam proses pembelajaran di sekolah-sekolah. Fasilitas perpustakaan yang baik dan lengkap akan mendukung kesuksesan proses pembelajaran. Pengabdian masyarakat yang dilaksanakan di Sekolah Menengah di wilayah Tanjung Duren Barat III No. 1 Jakarta, tepatnya Yayasan Pendidikan Al Chasanah bertujuan untuk berbagi pengetahuan atau transfer knowledge mengenai penerapan sistem informasi berbasis teknologi informasi sebagai pendukung pelayanan pendidikan kepada Guru dan Staf Pendidikan agar memahami dan berkemampuan untuk pengembangan pembelajaran sesuai kebutuhannya. Target khusus yang ingin dicapai adalah pemahaman dan kemampuan untuk menerapkan sistem informasi berbasis komputer sebagai pendukung pelayanan pendidikan di Yayasan Pendidikan Al Chasanah agar mampu menyesuaikan dari tuntutan dan kebutuhan dunia usaha dan dunia industri, sebagai pendukung dan sumber pustaka penyuluhan diberikan juga pada sisi pengimplementasian perpustakaan sekolah dan yayasan Al Chasanah dengan aplikasi open source SliMS Senayan. Adapun metode yang digunakan berbentuk penyuluhan dengan penyampaian yang praktis melalui transfer ilmu dan sajian peran dan fungsi dari aplikasi perpustakaan untuk meningkatkan pelayanan pendidikan sehingga benar-benar dapat diterima dan menambah esensi pengetahuan dan keterampilan Guru dan Pustakawan serta terutama untuk para siswa. Hasil dari kegiatan pengabdian pada masyarakat yang dilakukan oleh Tim P2M Fasilkom Universitas Esa Unggul yang diadakan di lingkungan sekolah yang berada dalam Yayasan Al Chasanah ini adalah adanya peningkatan dan pengembangan wawasan bagi para guru dan pustakawan terkait fungsi dan proses pengelolaan perpustakaan di lingkungan sekolah di bawah yayasan Al Chasanah. Ditambah dengan penggunaan software Sistem Informasi Perpustakaan opensource SliMS Senayan, fungsi dan proses pengelolaan perpustakaan sekolah bisa lebih dioptimalkan. Kata kunci : perpustakaan sekolah, open source, pustakawan